試合における大学男子硬式テニス選手のサーブ動作の分析: スタンス別ラケットスピード上位群と下位群の比較 - 河鰭, 真世; 阿江, 通良; 沼津, 直樹; 堀内, 健太郎; 杉田, 正明 (コーチング学研究, 2025)
The purposes of this study were to analyze serving motions of twenty-eight Japanese male college tennis players during matches and to compare kinematics for two racket speed groups of different foot-stance styles. Twelve players whose racket speed was higher than 39.00±3.67 m/s were classified as a high speed group and sixteen players with the lower one as a low speed group. The significant differences between the two groups were observed in the racket speed and ball speed. The players of the foot-up stance style showed differences between the high and low speed groups in the torso backward tilt and the hip flexion from toss-up to the forward-swing phase, and the right shoulder abduction angle during the serving motion. The foot-back style players showed differences between the two groups in the horizontal abduction angle of the right shoulder. The results suggested that the low group players of the foot-up style should reduce the backward tilt of the torso in the back-swing phase and raise the right arm in a later timing than the left arm, and that the foot-back style players should horizontally abduct the right shoulder in the forward-swing phase.